Spontaneous uterine rupture with placenta accreta at 17 weeks of pregnancy in a known case of systemic lupus erythematosus: a case report - Bharti, Kanishka; Patel, Sejal; Bhatia, Saral; Udhanawala, Parul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Over the past ten years, cases of uterine wall thinning and placental abnormalities complicated by Systemic Lupus Erythematosus (SLE) during pregnancy have been reported. Uterine rupture without prior scarring is uncommonly associated with SLE and prolonged steroid therapy. Long-term steroid use can lead to muscle degeneration; however, the exact mechanism behind myometrium thinning remains unknown. A retrospective case study of a patient with a known case of SLE admitted in a tertiary care centre of South Gujarat with spontaneous uterine rupture at 17 weeks of pregnancy. A qualitative analysis of the diagnosis and management procedures was done, offering a critical assessment of their effectiveness and the potential implications for future clinical practice. Systemic lupus erythematosus is an autoimmune disorder occurring mostly in females of reproductive age group. Genetic factors, altered B and T cell immunity, environmental factors, and production of auto-antibodies lies behind the pathogenesis of SLE. Long term steroid therapy may lead to decreased estrogen leading to uterine rupture. Extended use of systemic steroids in patients with SLE may elevate the risk of spontaneous rupture of an unscarred uterus. While abnormal placentation and uterine rupture are exceedingly rare, they necessitate timely diagnosis and early intervention